Analisis Kualitas Pelayanan Terhadap Kepuasan Penggunaan Jasa Kapal Penyeberangan Roll On Roll Off (Ro-Ro) Dumai-Rupat - Memori, Yuslin; Nugraha, Budi (Polyscopia, 2025)
This study aims to analyze the relationship between service quality and user satisfaction in Ro-Ro ferry services. The assessment indicators used in this research include tangibles, responsiveness, reliability, assurance, and empathy. A quantitative approach was employed, with data collected through observations, interviews, and questionnaires. The study population comprised all users of Ro-Ro ferry services, with sampling conducted using the incidental sampling technique. A total of 20 respondents participated, and the collected data were analyzed using SPSS V.27, applying validation and reliability tests. The findings reveal that all statements used to measure the studied variables are valid and reliable. Consequently, the instrument used in this study is considered high-quality, consistent, and interrelated. These results contribute to a better understanding of the factors influencing user satisfaction in ferry services.